2016
DOI: 10.1101/075747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of African, Asian, and American Zika Viruses in Swiss Webster mice: Virulence, neutralizing antibodies, and serotypes

Abstract: The sequence of Zika virus has evolved as it has spread out of Africa and into the Americas. It is unclear whether American strains of the virus define a new serotype. Here, we have tested the virulence and immunogenicity of three wild-type ZIKV strains in neonatal Swiss Webster mice. We found that all three ZIKV strains (African MR766, 1947; Asian FSS13025, 2010; and American, PRVABC59, 2015) are capable of killing neonatal mice after intracranial injection. Intraperitoneal injection with these viruses did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In contrast, sera of mice immunized with pcZIKME Br (SHP2015; Asian strain) showed 4-fold higher titers against homologous ZIKA Br -SRIPs than against heterologous ZIKV Af -SRIPs. These data are consistent with previous reports of mice immunized with different strains of ZIKV 20 , 21 and suggested that a neutralization assay using multiple ZIKV strains for detection of serological differences between the ancestral African strain and Asian strain might be useful to determine precisely ZIKV infection. It will be of interest to explore these associations with various ZIKV strains.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, sera of mice immunized with pcZIKME Br (SHP2015; Asian strain) showed 4-fold higher titers against homologous ZIKA Br -SRIPs than against heterologous ZIKV Af -SRIPs. These data are consistent with previous reports of mice immunized with different strains of ZIKV 20 , 21 and suggested that a neutralization assay using multiple ZIKV strains for detection of serological differences between the ancestral African strain and Asian strain might be useful to determine precisely ZIKV infection. It will be of interest to explore these associations with various ZIKV strains.…”
Section: Discussionsupporting
confidence: 92%
“…Somewhat greater differences in cross-neutralization of African and American Zika virus strains were observed in recent work with postinfection sera of mice (115). Specifically, antibodies induced by the American strain (PRVABC59) (2015) neutralized the African strain (MR766) (1947) 10-fold less potently than the homologous American strain.…”
Section: Zika Virus As a Single Serotypementioning
confidence: 87%
“…The A129 mouse is commonly used to study ZIKV because the virus has been shown to infect cells by targeting human STAT2 to suppress IFN signaling, and it has been proposed that since it does not bind murine STAT2, it cannot infect mice unless the type I IFN receptor is knocked out or blocked ( 1 ). Of additional note, the majority of investigations that utilize ZIKV grow their viral stocks in Vero cells, which do not produce IFN type I in response to a viral infection, and thus allows them to be permissive to ZIKV infections ( 103 , 104 ).…”
Section: Zikv Transmission and Tissue Tropismmentioning
confidence: 99%